Peran Online Customer Review dan Influencer Terhadap Keputusan Pembelian Produk Cushion Somethinc Melalui Mediasi Brand Trust - Nur Muhibah; Nurul Huda (Jurnal Mirai Management, 2026)
This study aims to examine the influence of Online Customer Review and Influencer on the Purchase Decision of Somethinc Cushion products, both directly and indirectly through Brand Trust as a mediating variable. Using a quantitative approach, the research involved 133 respondents who are users of Somethinc Cushion at Unniqestore Jepara, with data collected through Likert-scale questionnaires and analyzed using Partial Least Squares (PLS) via SmartPLS 3.0. The results indicate that Online Customer Review and Influencer have significant positive effects on Brand Trust and Purchase Decision. Brand Trust significantly mediates the influence of both Online Customer Review and Influencer on Purchase Decision, as shown by significant indirect effects. The model demonstrates strong explanatory power, with 60.8% of the variance in Brand Trust and 71% of the variance in Purchase Decision explained by the studied variables. These findings highlight the crucial role of brand trust in digital marketing strategies, emphasizing the importance of managing customer reviews and collaborating with credible influencers to strengthen consumer confidence and drive purchasing decisions.